1996
DOI: 10.1001/archneur.1996.00550060029011
|View full text |Cite
|
Sign up to set email alerts
|

Motor Changes in Presymptomatic Huntington Disease Gene Carriers

Abstract: These results suggest that subtle subclinical changes in motor function are present in presymptomatic individuals who have inherited the HD allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 16 publications
3
47
1
1
Order By: Relevance
“…Although some studies have shown processing speed to be the hallmark of early cognitive decline in HD (Kirkwood et al, 2000;Kirkwood et al, 1999;Siemers et al, 1996), others have shown different patterns of impairment. Lawrence et al (1998) examined cognitive task performance in 54 at-risk carriers of the HD mutation and found that they performed significantly worse than noncarriers on tasks of cognitive set-shifting and fluency, deficits attributed to inhibitory control mediated by striatofrontal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown processing speed to be the hallmark of early cognitive decline in HD (Kirkwood et al, 2000;Kirkwood et al, 1999;Siemers et al, 1996), others have shown different patterns of impairment. Lawrence et al (1998) examined cognitive task performance in 54 at-risk carriers of the HD mutation and found that they performed significantly worse than noncarriers on tasks of cognitive set-shifting and fluency, deficits attributed to inhibitory control mediated by striatofrontal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the saccadometry research tool has proved valuable in separating premanifest, manifest, and controls who showed an increased incidence of early saccades with unusually short latencies. [84][85][86][87][88][89] Manifest patients early in the course of their disease, exhibit reduced saccadic velocity, 78,81,90 impaired initiation of saccades, an increase in the frequency of square-wave jerks, and an increase in saccadic latencies, that is greater for voluntary than reflexive saccades. They have excessive distractibility during attempted fixation, even when specifically instructed to maintain fixation on a centrally located target.…”
Section: Clinical Ocular Motor Findingsmentioning
confidence: 99%
“…Firstly it seems that the impairment in voluntary movement is closely related to the functional disability experienced by patients [2,7,20,21], suggesting that a faithful marker of the movement abnormality may also reveal functional status. Secondly, motor deficits can be detected early in the disease process, even in presymptomatic gene-positive subjects [8,9,19], raising the possibility that an objective marker might be of use even in early disease. And finally, motor deficits progress in line with other clinical measures of disease stage [17,20,21], and correlate with the loss of striatal D2 binding on raclopride 11C PET [18].…”
Section: Introductionmentioning
confidence: 99%